Conscription in Britain, New Zealand, Australia and Canada during the Second World War - Littlewood, David (History compass, 2020)
During the early stages of the Second World War, the governments of Britain, New Zealand, Australia and Canada each adopted sweeping powers to conscript men into their respective armed forces. When conscription was subsequently extended to encompass productive as well as military activities, and made applicable to women as well as men, it quickly became a web that entangled every aspect of wartime life. However, the existing historiographies have focused largely on the political and institutional dimensions of these measures or have assessed their impacts by reference only to certain groups within society. Relatively little has been written about how populations as a whole were affected by conscription and how people from various walks of life responded to its many impositions. While a few scholars have started to upset these trends by producing wide-ranging social and cultural analyses, even their works have remained almost totally confined within national frameworks.